2020
DOI: 10.1186/s13075-020-2120-7
|View full text |Cite
|
Sign up to set email alerts
|

Adverse events during oral colchicine use: a systematic review and meta-analysis of randomised controlled trials

Abstract: Background: Colchicine is a widely used drug to treat inflammatory diseases. Due to its long historical use in medicine, controlled clinical trials have been small and there remains some caution with the use of this drug in patients with co-morbidities. The aim of the study is to systematically examine the side effect profile of colchicine in controlled clinical trials across all published indications. Methods: A systematic review was conducted in accordance with PRISMA methodology. The Cochrane Library, MEDLI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
92
1
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(120 citation statements)
references
References 48 publications
7
92
1
8
Order By: Relevance
“…Guo X. et al reported that CYP3A inhibition was associated with colchicineinduced hepatotoxicity in animals [28]. However, a meta-analysis study demonstrated that adverse liver events did not increase in gout patients with colchicine use [29]. The present study also revealed that the number of patients with hepatotoxicity was not significantly higher in colchicine users than non-users.…”
Section: Discussioncontrasting
confidence: 43%
“…Guo X. et al reported that CYP3A inhibition was associated with colchicineinduced hepatotoxicity in animals [28]. However, a meta-analysis study demonstrated that adverse liver events did not increase in gout patients with colchicine use [29]. The present study also revealed that the number of patients with hepatotoxicity was not significantly higher in colchicine users than non-users.…”
Section: Discussioncontrasting
confidence: 43%
“…Once colchicine is long-term used, it often brings side effects such as liver and kidney injury and gastrointestinal reactions. 42 Importantly, we have demonstrated that wedelolactone indeed suppressed caspase 1 (p20) and IL-1ÎČ expression in MSU-induced gouty arthritis. As wedelolactone might inhibit both the genes expression and the inflammasome activation in vivo to reduce the production of inflammatory cytokine, we mainly focused on the anti-inflammasome mechanism of wedelolactone, and MSU-induced inflammation was partly conducted to verify its role in inhibiting NLRP3 activation in vivo.…”
Section: Discussionmentioning
confidence: 72%
“…Diarrhoea occurred in 7.4% of treated patients, which is in line with data reported in the systematic review of the literature. 13 The main finding of this study was that patients treated with colchicine had a better survival rate as compared with SoC. We acknowledge that this result might be affected by a survival bias deriving from the inclusion in the colchicine group of patients who were 'survivors' at the moment of initiating the treatment with this drug.…”
Section: Discussionmentioning
confidence: 78%
“…12 The side effect profile of colchicine is widely known, with gastrointestinal symptoms occurring in up to 17% of patients, while severe organ manifestations being rare. 13 Based on the identification of HIS in patients with COVID-19 pneumonia and the anti-inflammatory properties of colchicine, we postulated the rationale of use of colchicine in patients admitted to the hospital for COVID-19.…”
Section: What Does This Study Add?mentioning
confidence: 99%